Low cost hexacopter autonomous platform for testing and developing photogrammetry technologies and intelligent navigation systems - Burdziakowski, Paweł (International Conference “Environmental Engineering”, 2017)
Low-cost solutions for autonomous aerial platforms are being intensively developed and used within geodetic community. Unmanned aerial vehicles are becoming very popular and widely used for photogrammetry and remote sensing applications. Today’s market offers an affordable price components for unmanned solution with significant quality and accuracy growth. Every year market offers a new solutions for autonomous platforms with better technical specifications. Commercial drones for amateurs are widely offered and presents a quality and accuracy not available in past few years. In this paper an autonomous open source low cost haxacopter system for photogrammetry and intelligent navigation technologies evaluation is being presented. The system was designed and assembled for technologies testing and for educational purposes. The drone is based only on open source hardware and software. All components are based on open source and commercial of the shelf products. That approach to the drones construction provides a many capabilities to test, implement and execute new algorithms, solutions and tasks. Providing basic configuration tools system enables students to safely perform elementary setup and testing. An advanced configurations system tool and open source structure enables to execute advanced scientific test and research. Paper presents results of designed process, system configuration and specification, technical issues that was being solved during test flights and practical research results.
Keywords: drone; uav; photogrammetry; navigation; open-source; pixhawk